2009
DOI: 10.1057/mel.2009.9
|View full text |Cite
|
Sign up to set email alerts
|

Port selection from a hinterland perspective

Abstract: The studies investigating the port selection process had one thing in common: they analyse the declared preferences of the port agents. However, it is difficult to identify the relevant variables in this process because of the heterogeneity of this group. In this article, we suggest to study the port choice through revealed port selection instead of asking port stakeholders about the main factors in port selection. We propose to analyse the actual inter-port traffic distribution from a holistic view using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 18 publications
(17 reference statements)
0
20
0
Order By: Relevance
“…Some of the studies used subjective data for the development of the methodology (Nir, Lin, & Liang, 2003;Tiwari, Itoh, & Doi, 2003;Wu, Liu, & Peng, 2014); other studies concentrated on existing data to develop their model (Garcia-Alonso & Sanchez-Soriano, 2009;Malchow & Kanafani, 2001;Malchow & Kanafani, 2004;Steven & Corsi, 2012;Tang, Low, & Lam, 2011;Veldman, Garcia-Alonso, & Vallejo-Pinto, 2011;Veldman & Bückmann, 2003); while (Magala & Sammons, 2008) presented a new port selection modelling approach based on a conceptual framework.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some of the studies used subjective data for the development of the methodology (Nir, Lin, & Liang, 2003;Tiwari, Itoh, & Doi, 2003;Wu, Liu, & Peng, 2014); other studies concentrated on existing data to develop their model (Garcia-Alonso & Sanchez-Soriano, 2009;Malchow & Kanafani, 2001;Malchow & Kanafani, 2004;Steven & Corsi, 2012;Tang, Low, & Lam, 2011;Veldman, Garcia-Alonso, & Vallejo-Pinto, 2011;Veldman & Bückmann, 2003); while (Magala & Sammons, 2008) presented a new port selection modelling approach based on a conceptual framework.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The PRs were calculated using AHP presented by Saaty [30]. We have ranked our five departing and eight destination ports according to eleven different criteria, explained in [9,31,7,32,33]. To obtain relevant data, a survey among several Bavarian logistics service providers, shippers, shipping lines and retailers was conducted.…”
Section: Assumptions Of the Modelling Approachmentioning
confidence: 99%
“…The port choice problem has been studied a lot since Sargent [6] suggested that cargo tends to seek the shortest route to access the sea. The problem is of particular interest in the multiport regions of North-Europe, the North-Adriatic, the North-Mediterranean and East and Southeast Asia, where the interport competition has intensified in recent years [7]. Therefore, port choice studies were made mostly for multi-port regions.…”
Section: Introductionmentioning
confidence: 99%
“…In most of the cases the captive hinterlands were downgraded to contestable hinterlands where there is no single port with a clear cost advantage over competing ports. As a consequence of this fact the interport competition has encountered an enormous increase of volume in the last few years [4]. In practice, this means that maritime transport users can choose any feasible port in the area.…”
Section: Introductionmentioning
confidence: 99%